Everyday Aesthetics and Eighteenth-Century Fiction: Defoe’s Robinson Crusoe and Richardson’s Sir Charles Grandison - Kraft, Elizabeth (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2022)
This essay employs strategies drawn from the emergent field of everyday aesthetics to explore the pleasures of reading Daniel Defoe’s Robinson Crusoe and Samuel Richardson’s Sir Charles Grandison. As a fictional paradigm, Crusoe has been a paradoxical inspiration, inviting critique as a seductive representative of colonial power, on the one hand, and eliciting admiration for his ability to provoke meaningful artistic and intellectual engagement from a diverse group of writers and thinkers, on the other hand. To many ordinary readers, he has proved company worth keeping as a source of inspiration and personal pleasure primarily through his aesthetic approach to the structuring of everyday life. The fiction of Samuel Richardson continues the focus on the everyday, placing even greater emphasis on the relationship between the ethical and the aesthetic. In his final novel, Sir Charles Grandison, pleasure can scarce be felt without some commentary outlining the contours of moral significance, and the very act of moral reasoning is demonstrably affective for characters and readers alike. The essay ends with consideration of the power of literature, especially the realistic novel, to shape the ordinary lives of everyday readers.